Gastrointestinal symptoms and association with medication use patterns, adherence, treatment satisfaction, quality of life, and resource use in osteoporosis: baseline results of the MUSIC-OS study. Issue 3 (March 2016) - Modi, A.; Sen, S.; Adachi, J.; Adami, S.; Cortet, B.; Cooper, A.; Geusens, P.; Mellström, D.; Weaver, J.; Bergh, J.; Nguyen, A.; Sajjan, S.
Abstract Summary The Medication Use Patterns, Treatment Satisfaction, and Inadequate Control of Osteoporosis Study (MUSIC-OS) is a prospective, observational study of women with osteoporosis in Europe and Canada. At baseline, patients with gastrointestinal symptoms reported lower adherence to osteoporosis treatment, treatment satisfaction, and health-related quality of life, than those without gastrointestinal symptoms. Introduction The aim of the study was to examine gastrointestinal (GI) symptoms and the association between GI symptoms and treatment adherence, treatment satisfaction, and health-related quality of life (HRQoL) among osteoporotic women in Europe and Canada. Methods Baseline results are reported here for a prospective study which enrolled postmenopausal, osteoporotic women who were initiating (new users) or continuing (experienced users) osteoporosis treatment at study entry (baseline). A patient survey was administered at baseline and included the occurrence of GI symptoms during 6-month pre-enrolment, treatment adherence (adherence evaluation of osteoporosis (ADEOS), score 0–22), treatment satisfaction (Osteoporosis Treatment Satisfaction Questionnaire for Medications (OPSAT-Q), score 0–100) and HRQoL (EuroQol-5 dimension (EQ-5D) utility, score 0–1; OPAQ-SV, score 0–100). The association between GI symptoms and ADEOS (experienced users), OPSAT-Q (experienced users), and HRQoL (new and experienced users) was assessed by general linear models adjusted for patient characteristics. Results A total of 2959 patients (2275 experienced and 684 new users) were included. Overall, 68.1 % of patients experienced GI symptoms in the past 6 months. Compared with patients without GI symptoms, patients with GI symptoms had lower mean baseline scores on most measures. The mean adjusted differences were ADEOS, −0.43; OPSAT-Q, −5.68; EQ-5D, −0.04 (new users) and −0.06 (experienced users), allP  < 0.01. GI symptoms were also associated with lower OPAQ-SV domain scores: physical function, −4.17 (experienced users); emotional status, −4.28 (new users) and −5.68 (experienced users); back pain, −5.82 (new users) and −11.33 (experienced users), allP  < 0.01. Conclusions Patients with GI symptoms have lower treatment adherence and treatment satisfaction and worse HRQoL than patients without GI symptoms.